2019
DOI: 10.4236/nr.2019.107018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment and Trend of Land Cover Land Use Changes in Owerri and Environs, South Eastern Nigeria

Abstract: This study examined land cover and land use changes (LCLUC) in Owerri and environs from 1986 to 2016 and went further to determine the trend in the change of each LCLUC class. The satellite imagery of the area over the three decades was characterized into the different LCLUC classes and the changes in the areal extent of the different LCLUC classes were calculated and plotted, followed with the estimation of the trend using linear regression analysis method. The result revealed that over the three decades, for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…Figure 1 depicts the map of the research region. Owerri serves as the principal centre for economic and industrial activities in Imo State, resulting in a significant growth in urbanisation in neighbouring rural communities and other states (Echebima et al, 2019).…”
Section: Geographical and Demographic Overview Of The Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 depicts the map of the research region. Owerri serves as the principal centre for economic and industrial activities in Imo State, resulting in a significant growth in urbanisation in neighbouring rural communities and other states (Echebima et al, 2019).…”
Section: Geographical and Demographic Overview Of The Study Areamentioning
confidence: 99%
“…Despite growing concerns about the effects of LULCC on sustainable development and the environment, research on LULCC in southeastern Nigeria has only recently begun (Echebima et al, 2019). The majority of existing LULCC research in the region has concentrated on specific areas, with major cities garnering attention for urban sprawl dynamics Uko & Offiong, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Urbanization transforms rural areas to urban within a decade resulting in the increased absorption of solar radiation, a decrease of evapotranspiration, and a release of anthropogenic heat, thereby resulting in a change of air temperatures, horizontal winds, and air quality. Several studies have shown that land use changes induce climate change [13] [14].…”
Section: Introductionmentioning
confidence: 99%